Physico-chemical properties of mixed jam from pineapple and sweet gourd (Journal of the Bangladesh Agricultural University, 2018)
This study investigated the preparation of mixed jam from sweet gourd and pineapple. The proximate compositions of sweet gourd pulp were: moisture content 90.3%, ash 0.33%, sugar 3.24% and ascorbic acid 2.97 mg/100g. Pineapple pulp contained 74.6%moisture, 0.3%ash, 9.95% sugar and 78.79 mg/100 gascorbic acid. The keeping quality and shelf life of the prepared mixed jam were studied. For the case of mixed jam, the highest sugar content (62.54%) was in sample with 60% pineapple and 40% sweet gourd. Organoleptic test showed that overall acceptability of 60% pineapple +40% sweet gourds was better than that of other mixed jam. The highest score (8.0) was found from the sample with 60% pineapple + 40% sweet gourd, and the lowest score (6.0) was from the sample with 50% pineapple + 50% sweet gourd. During storage period, TSS, reducing sugar, non-reducing sugar and pH decreased for all cases. Fading of color was observed at 90 days of storage for some samples.J. Bangladesh Agril. Univ. 16(2): 309-314, August 2018